Comparison of Sectoral Structure-Function Relationships in Glaucoma: Vessel Density Versus Thickness in the Peripapillary Retinal Nerve Fiber Layer - Sakaguchi, Kimikazu; Higashide, Tomomi; Udagawa, Sachiko; Ohkubo, Shinji; Sugiyama, Kazuhisa (Investigative ophthalmology & visual science, 2017)
To compare the sectoral structure-function relationships in glaucoma between two structural parameters, vessel density (VD) and thickness, in the peripapillary retinal nerve fiber layer (RNFL). Optical coherence tomography (OCT) angiography (AngioVue/RTVue-XR) for VD and OCT (RS-3000) for peripapillary RNFL thickness were performed in 129 eyes from 129 subjects (94 glaucoma, 17 glaucoma suspects, and 18 normal eyes). Humphrey visual field (VF) tests were performed using a SITA standard 24-2 program. Sectoral structure-function relationships based on the Garway-Heath map were compared between VD and thickness using a semipartial correlation coefficient (sr) and partial residual plots determined by multiple linear regression models controlling for the effects of sex, age, axial length, disc area, beta- and gamma- parapapillary atrophy (PPA) zones, and signal strength index (SSI). For all VF sectors, the sr2 of VD was largest when the VD sector corresponded to the VF sector (sr2: 0.17-0.39). In contrast, in only three sectors was the sr2 of thickness largest when the thickness sector corresponded to the VF sector (sr2: 0.02-0.34): the inferior temporal, temporal, and superior temporal sectors. The partial residual plots against VD showed more linear relationships with VF sensitivity than those against thickness in the qualitative evaluation of fitting by locally weighted scatterplot smoothing. Eyes with larger SSI had higher VD, whereas eyes with a larger extension of the PPA zone into the VD measurement area had lower VD. Peripapillary RNFL VD and thickness have different characteristic sectoral structure-function relationships in glaucoma.